PENGGUNAAN SLANG BAHASA INGGRIS OLEH ANAK MUDA DI KOTA MALANG - Rumagit, Tannia Christina; Rambing, Rosalina (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTÂ This research entitled â€œThe Usage of Slang by Millennial in Malangâ€. The aims of this research are to identify the usage of slang by millennial in Malang to describe their forms and meanings.The usage data were collected from Millennial in Malang. The collected data were analysed using a descriptive methods introduce by Bloomfield (1933), Guth (1961), and Fishman (1971). Practically, this research may provide good comprehension to the readers about the forms of the usage of slang by millennial in Malang. The results show that the forms of the usage of slang are facetious mispronunciation, shortened forms, interjection, figurative expressions and nick name. In terms of meaning, the usage of slang by millennial in Malang words were analysed and translated according to the context used by using Urban Dictionary.As a conclusion. The millennial in Malang used slangsÂ  for their daily conversation. Especially millennial in Roemah Kantja coffee house, their used slangs to talk with each other in every situation.Â Keywords : slang, millennial, malang, sosiolinguistic